Anomalous dewetting growth of Si on Ag(111). Issue 39 (27th September 2022) - Kawakami, Naoya; Arafune, Ryuichi; Minamitani, Emi; Kawahara, Kazuaki; Takagi, Noriaki; Lin, Chun-Liang
Abstract : We demonstrate the novel growth of silicene grown on Ag(111) using STM and reveal the mechanism with KMC simulation. Abstract : We demonstrate the novel growth of silicene grown on Ag(111) using STM and reveal the mechanism with KMC simulation. Our STM study shows that after the complete formation of the first layer of silicene, it is transformed into bulk Si with the reappearance of the bare Ag surface. This dewetting (DW) during the epitaxial growth is an exception in the conventional growth behavior. Our KMC simulation reproduces DW by taking into account the differences in the activation energies of Si atoms on Ag, silicene, and bulk Si. The growth modes change depending on the activation energy of the diffusion, temperature, and deposition rate, highlighting the importance of kinetics in growing metastable 2D materials.